Double inductor system as tool to flat stamping of thin-walled metals - Shinderuk, S.; Nagi Masoud, S.; Шиндерук, С. О.; Нажи Масуд, C.; Шиндерук, С. А. (Харківський національний автомобільно-дорожній університет, 2014)
The effective application of magnetic-pulse technologies in motor industry is proved. The analysis of a double inductor system as a tool of the flat stamping of thin-walled metals is made, its efficiency and effectiveness are proved.
Спарена індукторна система – інструмент для плоского штампування тонкостінних металів
Спаренная индукторная система – инструмент для плоской штамповки тонкостенных металлов
Keywords: magnetic-pulse metal treatment; magnetic field; inductor system; workpiece; intensity; flat stamping; магнітно-імпульсна обробка металів; магнітне поле; індукторна система; заготовка; напруженість; плоске штампування; магнитно-импульсная обработка металлов; магнитное поле; индукторная система; заготовка; напряженность; плоская штамповка; 621.318.4